Effect of UNAGI (Nutrition Snakes and Ladders Game) on Knowledge of Balanced Diet and Nutritional Intake in Adolescents in Bekasi - Fayasari, Adhila; Juanita, Elizabeth (Indonesian Journal of Human Nutrition, 2023)
Indonesia still faces the Triple Burden of Malnutrition, which can impact the dietary choices of adolescents to balance their nutritional intake and, simultaneously, emphasize the need for effective nutrition education. This study aimed to determine the effect of nutrition education delivered through the UNAGI game and videos on knowledge and nutritional intake of high school students. This quasi-experimental study was conducted with students from Public Senior High School 12 in Bekasi City, where the participants were divided into intervention and control groups. The intervention was provided once a week for two consecutive weeks. Knowledge was measured using a questionnaire, and food intake was assessed through 24-hour food recall. Data were analyzed using the Mann-Whitney test for the difference between groups and paired t-test/Wilcoxon for pre-post comparisons, with α significant level of 5%. Before the intervention, there was no significant difference in knowledge and dietary intake between the two groups. Post-intervention, a significant improvement in nutrition knowledge (p-value of 0.000) was noted in the intervention group exposed to the snake and ladder nutrition game. However, there were no significant changes in energy intake (p-value of 0.162), fat intake (p-value of 0.144), sugar consumption (p-value of 0.066), and salt consumption (p-value of 0.944). The findings support the recommendation of utilizing UNAGI games for nutrition education in the digital era as a valuable alternative to visual media, effectively contributing to enhanced nutritional understanding among adolescents.